2004
DOI: 10.1074/jbc.m406467200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Embryonic Stem Cell Self-renewal by Phosphoinositide 3-Kinase-dependent Signaling

Abstract: The maintenance of murine embryonic stem (ES) cell self-renewal is regulated by leukemia inhibitory factor (LIF)-dependent activation of signal transducer and activator of transcription 3 (STAT3) and LIF-independent mechanisms including Nanog, BMP2/4, and Wnt signaling. Here we demonstrate a previously undescribed role for phosphoinositide 3-kinases (PI3Ks) in regulation of murine ES cell self-renewal. Treatment with the reversible PI3K inhibitor, LY294002, or more specific inhibition of class I A PI3K via reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

28
409
1
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 384 publications
(447 citation statements)
references
References 50 publications
28
409
1
4
Order By: Relevance
“…20 Inhibition of PI3K/Akt signaling with LY-294002 reduces mouse ES proliferation, pluripotency, and Nanog expression. 18,19,21,22 Those effects are similar to the effects of overexpressing DLK in mouse ES cells ( Fig. 3C and D).…”
Section: Dlk Kinase Activity Is Upregulated Upon Differentiation Of Msupporting
confidence: 69%
See 3 more Smart Citations
“…20 Inhibition of PI3K/Akt signaling with LY-294002 reduces mouse ES proliferation, pluripotency, and Nanog expression. 18,19,21,22 Those effects are similar to the effects of overexpressing DLK in mouse ES cells ( Fig. 3C and D).…”
Section: Dlk Kinase Activity Is Upregulated Upon Differentiation Of Msupporting
confidence: 69%
“…[18][19][20][21][22] Many proteins and signaling pathways involved in proliferation or pluripotency are modulated by PI3K/Akt including Gsk3b/Myc, FoxO, mTOR and Tbx3/Nanog pathways. 8,21,22,41-43, In this study, for the first time, DLK was demonstrated to be an Akt substrate.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathway from LIF stimulation to the inactivation of GSK-3β through the phosphoinositide 3-kinase (PI3K)/Akt pathway has been described in ES cells [20]. However, neither stimulation with LIF or short-term treatment with a PI3K inhibitor, LY294002, showed any effect on the stability of β-catenin, although long-term treatment (around five days) of LY294002 did reduce β-catenin phosphorylation.…”
Section: Discussionmentioning
confidence: 99%